Rapid Determination of All-Solid-State Battery Performance via Chronoamperometry. Issue 9 (1st September 2022) - Yanev, S.; Auer, H.; Heubner, C.; Höhn, S.; Nikolowski, K.; Partsch, M.; Michaelis, A.
Abstract : All solid-state batteries (ASSBs) are considered among the most promising next-generation energy storage devices but are currently still limited in terms of performance. To advance the development process in an efficient way, appropriate characterization methods are needed. Herein, we demonstrate chronoamperometry to rapidly evaluate the performance of ASSBs. Examples are given using argyrodite solid electrolyte together with various cathode active materials. It is shown that chronoamperometry provides equivalent rate capability information to common galvanostatic testing procedures, while being much simpler and significantly faster (e.g. by a factor between 8 and 33 for the tested materials). The high data density allows accurate model-based analysis to identify the rate limiting mechanism, such as electrical or diffusion limitations, and to determine the active material utilization at very low rates. An effective C-rate is proposed, which describes the rate performance of the utilizable active material. The observed electrode- and active material-specific performance differences are explained by morphological effects, supported by scanning electron microscopy analyses of the cathode cross sections. The results demonstrate the ability of chronoamperometry to rapidly quantify electrochemical performance and provide a deeper understanding of the limitations of ASSBs.